Badania Równania Naviera-Stokesa w Centrum Obliczeniowym Akademii Nauk ZSRR - Dorodnicyn, A.A.; Lulka, V.A.; Meller, N.A. (Engineering Transactions, 1972)
Three methods are used for the numerical solution of Navier-Stokes equations: 1) «stationary method» of successive approximations, 2) non-stationary «artificial» method and 3) non-stationary «real» method. The boundary conditions used are in all cases the same. Th.cy are presented in such a form that the equations for vorticity ω and stream function VI are separated. Some results of computations are presented. The calculations have been carried out for the largest possible Re numbers. It was found in some cases that when Re-number reached the order of a few hundreds, all the methods become divergent. The second important problem considered is the accuracy of numerical calculations for the flow with large Re-numbers.